Copyright and multimedia products : a comparative analysis - Stamatoudi, Irini A. (Cambridge ; New York : Cambridge University Press, 2002)
Multimedia products have experienced tremendous market success. Yet too often they are given inadequate protection under existing national and international copyright schemes. Irini Stamatoudi provides a comprehensive, comparative treatment of multimedia works and copyright protection in this clear and concise volume. A detailed introduction outlines the nature of the multimedia work, as well as the scope of existing legislation; separate chapters consider collections and compilations, databases, audiovisual works and computer programs (video games are here treated as a 'test case'). Stamatoudi then analyses issues of qualification, regime of protection, and offers a model for a European legislative solution. Copyright and Multimedia Products will interest academics and students, as well as practitioners and copyright policy makers.
Cover; Half-title; Series-title; Title; Copyright; Dedication; Contents; Acknowledgments; Abbreviations; Introduction; 1 Placing multimedia products within the scope of copyright; 2 The scope of multimedia works; 3 Traditional literary works; 4 Collections and compilations; 5 Databases; 6 Audiovisual works; 7 Computer programs; 8 Video games as a test case; 9 Multimedia products and existing categories of copyright works; 10 A regime of protection for multimedia products; 11 Conclusions; Postscript; Bibliography; Index
Includes bibliographical references (pages 283-314) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Copyright -- Interactive multimedia; Copyright -- Audio-visual materials; Copyright and electronic data processing; Intellectual property; Copyright; Audio-visual materials -- Law and legislation; Intellectual Property; Copyright; Droit d'auteur.; Droit d'auteur et informatique; Multimédia -- Droit; Audiovisuel -- Droit; Propriété intellectuelle; Droit d'auteur -- Multimédias interactifs; Droit d'auteur -- Documents audiovisuels; intellectual property; copyright; LAW -- Intellectual Property -- Copyright; Audio-visual materials -- Law and legislation; Copyright; Copyright and electronic data processing; Copyright -- Audio-visual materials; Intellectual property; Electronic books; Interactive multimedia